(untitled) (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The article considers social and communicative culture as a fundamental component of the professionalism of future social workers. The main function of social and communicative culture, which is to establish emotional interaction and communication with clients, is distinguished. Attention is drawn to the fact that the formation of social and communicative culture is an important task of future social workers’ training. The theoretical and methodological basis of social and communicative culture of the personality, in particular, of future social workers, is investigated. The approaches of scientists to understanding the essence of the concept of ’culture’, ’culture of communication’, ’social-communicative culture’, ’social-communicative culture of a social worker’ are analyzed. The relationship between the features of social work and the quality of mastering the communication skills are the basis for the professional competence of the social worker has been clarified. The essence of the content of the social- communicative culture of the future social worker is revealed through the focus on ethics and humanization of professional relations, realization of the formed moral convictions, ideals and cultural values, and the structure of the social-communicative culture of future social workers is characterized. The fundamental importance of social and communicative culture has been identified as future professionals need to be trained to establish linguistic contact with clients, perceive professionally, understand and use information, clarify real problems of clients, and influence them effectively.